SOSIALISASI PERLINDUNGAN HUKUM TERHADAP HAK WARIS ANAK ANGKAT DALAM PERSPEKTIF HUKUM ISLAM DI CILAMAYA KARAWANG - Pahroji, Dedi; Kurniati, Grasia; Zubaedah, Rahmi; Abidin, Jaenal; Priyana, Puti (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service activity is to inform the relevant community about the inheritance rights of adopted children according to Islamic law. This dedication will benefit the people of Cilamaya Village, Karawang Regency because the large enough population does not rule out the possibility of inheritance problems, including the inheritance rights of adopted children. It can also increase opportunities and problems in the field of education, which is at the core of community service. In addition to conducting socialization, service implementers also help MSMEs in Cilamaya village. This program was carried out offline and was attended by village officials and PKK mothers. The socialization activities carried out by the service implementers during the minggonan discussed the inheritance of adopted children and MSMEs. Lectures, focused discussions with the community, and Q&A attended by all parties involved are used. The development of Islamic law (Tahrij al-ahkam 'alanash qanun) in rulings (jurisprudence) and ijtihad of judges of Religious Courts on the development of inheritance law in the Compilation of Islamic Law (KHI) can serve as a source of law, and this is relevant in the field of building legal material regarding inheritance in accordance with Islamic inheritance law. Therefore, the decision of the Religious Court judge greatly affects the legal protection of the Muslim community in the implementation of inheritance in accordance with Islamic inheritance law. In the case of MSMEs, this community service begins with material about productivity and competitiveness. Then, strengths, weaknesses, opportunities, and threats to MSMEs will be discussed further. The goal is to blend theory with reality in the real world. Therefore, conclusions can be made and the best solution for MSMEs to remain competitive in running their business.